Burkina Faso : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Modification of Performance Criteria; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burkina Faso. (IMF Staff Country Reports; Country Report ;, 2009)
This paper focuses on the Fourth Review for Burkina Faso under the Poverty Reduction and Growth Facility program. All quantitative performance criteria were met, notably the targets for the fiscal deficit, revenues, and social expenditure. The authorities reiterated their commitment to reforming tax policy. Despite progress on preparation, some delays have occurred because of delays in delivery of technical assistance, inadequate domestic capacity, and the challenging external context. The priority for 2009 is to sustain the reform momentum in a difficult environment.